Report of the Managing Director to the International Monetary and Financial Committee on the IMF's Policy Agenda : IMF Responses to Global Economic Challenges. (Policy Papers; Policy Paper ;, 2008)
The report provides an update on work in the following areas: global stability, IMF lending, food and fuel price developments, and modernizing the IMF.